COMMUTERS e MARAUDERS: tipologia de criminosos em série a partir de padrões de deslocamento para cometimento de delitos - Antônio Hot Pereira de Faria; Alexandre Magno Alves Diniz; Diego Filipe Cordeiro Alves (Confins)
The objective of this paper is to use empirical data obtained from official sources (police reports) to report the types of serial offenders operating in Belo Horizonte for their areas of activity. From the theoretical approaches on the subject, the study defined as an object of study (serial criminals) with the space-time cut in Belo Horizonte, from 01/01/2011 to 12/31/2013 and the categories of crimes and misdemeanors penalties, as defined in Brazilian legislation with at least 4 events in the period analyzed. For the identification between the commuters and marauders typologies, the spatial distribution of the events and the authors' place of residence were verified, using as a parameter the methodology proposed by Canter and Larkin (1993). The results indicated that there is a specific type of spatial behavior for each serial criminal, with no predominance of typology in quantitative terms. There was no increase in criminal outreach for a longitudinal series of events. On average, it has been shown that offenders who travel greater distances to commit their crimes have a tendency to concentrate their crimes in a certain area, the case of the commuter, rather than spreading over a specific area, as it seems to be more typical of the marauder.